Indutores de impacto ambiental : um estudo sobre a América Latina - Silva, Caroline Silva da (2015)
This survey estimated through STIRPAT model and panel data which inductors of the total CO2 emissions for Latin America, from 1970 to 2010. Therefore, the option chosen was the estimation of four models, one without fixed effects and others with fixed effects for countries, years and years and countries. As a result we obtained that the total population and urban population are the main drivers of total CO2 emissions, while the economically active population has a negative effect on CO2 emissions.